2020
DOI: 10.1111/ajd.13307
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous leiomyosarcoma: dermal and subcutaneous

Abstract: Background and objectives: Leiomyosarcoma of skin (LMS) can be sub-classified on pathology appearances as Dermal or Subcutaneous. The aim of this study was to provide treatment recommendations for these uncommon tumours. Methods: A retrospective review of all patients with dermal and subcutaneous leiomyosarcoma managed at the Peter MacCallum Cancer Centre, Australia from January 2003 to December 2018 was performed. Eighty-three patients were identified (64 dermal leiomyosarcoma, 19 subcutaneous leiomyosarcoma)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
18

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 19 publications
0
16
0
18
Order By: Relevance
“…We revealed that subcutaneous LMS and high grade tumors have a poorer prognosis than their counterparts. Several retrospective studies focused on LMS of the skin revealed that subcutaneous LMS had a higher risk of DM and mortality than cutaneous LMS [ 22 24 ]. Moreover, several previous studies demonstrated that tumor grade was one of the strong prognostic factors for all-site LMS [ 25 ] and genitourinary STS [ 2 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…We revealed that subcutaneous LMS and high grade tumors have a poorer prognosis than their counterparts. Several retrospective studies focused on LMS of the skin revealed that subcutaneous LMS had a higher risk of DM and mortality than cutaneous LMS [ 22 24 ]. Moreover, several previous studies demonstrated that tumor grade was one of the strong prognostic factors for all-site LMS [ 25 ] and genitourinary STS [ 2 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…El LMSC supone en torno al 2-3% de los sarcomas cutáneos y menos del 0.05% del total de las neoplasias cutáneas 1 . El LMSC dérmico se origina del músculo erector del pelo, el dartos genital o areolar, mientras que el subcutáneo se origina de la capa muscular de los vasos del tejido celular subcutáneo y los casos metastásicos cutáneos suelen tener un origen visceral, con predominio retroperitoneal 1,2 . El LMSC dérmico se define como aquella tumoración predominantemente dérmica con o sin invasión limitada del tejido celular subcutáneo.…”
Section: Discussionunclassified
“…El LMSC dérmico se define como aquella tumoración predominantemente dérmica con o sin invasión limitada del tejido celular subcutáneo. Algunos autores subdividen este grupo en tumor atípico intradérmico de músculo liso, con prácticamente nula capacidad de extensión a distancia, y leiomiosarcoma «dérmico» con posible extensión al tejido celular subcutáneo y mínima capacidad metastásica 2,3 . Los tumores predominantemente subcutáneos, que pueden llegar a comprometer la fascia o extenderse de forma limitada a la dermis, son considerados leiomiosarcomas subcutáneos.…”
Section: Discussionunclassified
See 2 more Smart Citations